Stachyops, a new nototanaid genus (Crustacea: Peracarida: Tanaidacea) from New Zealand, with remarks on nototanaid and tanaissuid phylogeny - Bird, Graham J. (Zootaxa, 2012)
A new genus and species, Stachyops sebparri, is described from the eulittoral of Cook Strait, New Zealand and is the firstrecord of a nototanaid from one of the main islands. A very small species, it has several morphological characters that areshared with some species of the Tanaissuidae, such as a narrow mandibular molar and fewer pereopods 4–6 carpal spines,yet retains some apparent plesiomorphic features more typical of the Nototanaidae or other ‘basal’ paratanaoideans. Aphylogenetic analysis does group it with the Nototanaidae sensu Bird & Larsen, but more phylogenetic studies of these two families are needed to clarify their composition, relationships, and validity.